PENGARUH FEE BASED INCOME (FBI) TERHADAP TINGKAT RETURN ON ASSET (ROA) DI PT. BANK SYARIAH MANDIRI - Iqbal Rafiqi; Nor Lailina Ulfa (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2022)
Fee Based Income is still a struggle between a bank and another. Not the least of all banks in Indonesia who don’t want Fee Based Income. Therefore, this research aims 1). to found out whether fee-based income has an effect on the rate of Return On Assets (ROA) at PT. Bank Syariah Mandiri 2). to found out how much the effects of Fee Based Income at Bank Mandiri Syariah. This research was a quantitative approach, with PLS data analysis. The type of simple linear regression analysis statistic to proved the effect of Fee Based Income on the rate of Return On Assets (ROA) at PT. Bank Syariah Mandiri. The research data was secondary data. The sample used the quarterly financial reports of PT. Bank Syariah Mandiri which is accessed from the internet. The research results show that Fee Based Income on the rate of Return On Assets have a significant effect, but it’s very low. Meanwhile, the amount of influence of Fee Based Income on the rate of Return On Assets at Bank Syariah Mandiri with a percentage value of 0.10%. which means that the ROA variable can be explained by the Fee Based Income variable of 0.10%. While the remaining 0.90% (100%-0.10%) is explained by other variables that are not the focus of the study.